Optimal gestational weight gain to reduce the risk of hypertension disorders of pregnancy among women with obesity: A single tertiary referral center study in Japan. Issue 11 (27th July 2022) - Sugeno, Misa; Kyozuka, Hyo; Murata, Tsuyoshi; Hiraiwa, Tsuyoshi; Jin, Toki; Fujimori, Mimori; Fukumoto, Yuki; Ito, Fumihiro; Suzuki, Daisuke; Toma, Fukuda; Yasuda, Shun; Fujimori, Keiya; et al.
Abstract: Aim: To examine the effect of weight gain during pregnancy on hypertension disorders of pregnancy among women with a prepregnancy body mass index ≥30.0 kg/m 2 . Methods: This retrospective cohort study included 257 Japanese women (116 primipara; 141 multipara) with singleton pregnancies with a prepregnancy body mass index ≥ 30.0 kg/m 2, who gave birth during 2013 to 2020 at Ohta Nishinouchi Hospital. Multiple logistic regression analyses were performed to identify the effect of gestational weight gain on early‐onset (<34 weeks), late‐onset (≥34 weeks), and overall hypertension disorders of pregnancy. Results: The prevalence of hypertension disorders of pregnancy in primiparas and multiparas was 28.4% and 11.3%, respectively. By multiple logistic regression analysis, gestational weight gain during pregnancy increased the risk of early‐onset (adjusted odds ratio: 1.20, 95% confidence interval: 1.03–1.39, p  < 0.05) and overall hypertension disorders of pregnancy (adjusted odds ratio: 1.12, 95% confidence interval: 1.03–1.22, p  < 0.05) among primiparas. Based on receiver operating characteristic curve analyses for early‐onset (area under the curve 0.67, 95% confidence interval: 0.56–0.78; p  < 0.05) and overall hypertension disorders of pregnancy (area under the curve 0.76, 95% confidence interval: 0.61–0.91; p  < 0.05) among primiparas, we determined the cut‐off weight gain during pregnancy for early‐onset and overall hypertension disorders of pregnancy as 3.85 kg, with sensitivity/specificity of 0.76/0.59 and 0.91/0.53, respectively. Conclusion: We recommend that the optimal gestational weight gain for reducing HDP be under 3.85 kg. This information may facilitate personalized pre‐conception counseling among women with obesity.